2017
DOI: 10.1302/2058-5241.2.160027
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric bone and joint infection

Abstract: Despite advances in understanding and management, paediatric osteoarticular infections continue to pose diagnostic difficulties for clinicians. Delays in diagnosis can lead to potentially devastating morbidity.No single investigation, including joint aspiration, is sufficiently reliable to diagnose conclusively paediatric bone and joint infection. Diagnosis should be based on a combination of clinical signs, imaging and laboratory investigations. Algorithms should supplement, and not replace, clinical decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 58 publications
3
98
0
17
Order By: Relevance
“…Acute hematogenous osteomyelitis (AHO) is particularly common in children <5 years of age and typically affects the metaphysis because of the rich but slow blood flow of the growing bone. 4 The microorganisms enter the bone via the nutrient artery and are lodged in the metaphyseal capillary loops where they begin to proliferate, resulting in the spread of inflammation. In neonates and children aged <18 months, the metaphyseal vessel loop and epiphyseal vessel are connected via transphyseal vessels traversing across the growth plate.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Acute hematogenous osteomyelitis (AHO) is particularly common in children <5 years of age and typically affects the metaphysis because of the rich but slow blood flow of the growing bone. 4 The microorganisms enter the bone via the nutrient artery and are lodged in the metaphyseal capillary loops where they begin to proliferate, resulting in the spread of inflammation. In neonates and children aged <18 months, the metaphyseal vessel loop and epiphyseal vessel are connected via transphyseal vessels traversing across the growth plate.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…5 Early diagnosis and appropriate treatment of osteomyelitis are imperative to avoid serious morbidity and permanent disability. 4…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus is a gram‐positive facultatively anaerobic bacterium and important pathogen in bone disease. It is responsible for about 70% of cases of osteomyelitis and 80% of joint infections in patients with rheumatoid arthritis and several other bone diseases . S. aureus infection of bone is associated with rapid, localized destruction of the tissue.…”
mentioning
confidence: 99%
“…It is responsible for about 70% of cases of osteomyelitis and 80% of joint infections in patients with rheumatoid arthritis and several other bone diseases. [1][2][3][4] S. aureus infection of bone is associated with rapid, localized destruction of the tissue. Studies have reported the internalization of S. aureus by both epithelial and endothelial cells.…”
mentioning
confidence: 99%